Rancang Bangun Antena Helix 8 Lilitan untuk Sistem Autotracking sebagai Penjejak Unmanned Aerial Vehicle (UAV) - Yenniwarti Rafsyam; Jonifan Jonifan; Panji Ibrahim N Ibrahim N (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2017)
Technological developments have already penetrated low current at the time of flight of unmanned or commonly called the Unmanned Aerial Vehicle (UAV), which humans no longer need to make direct contact with the spacecraft flight to fly missions such as air monitoring in the form of realtime video. In doing missions flown required good communication and stable in order to avoid loss of signal during the communication process takes place. So we need a reliable telecommunications equipment to meet these needs, one of which is the antenna. In this final project designed three pieces of helix antenna coil 8 which works at a frequency of 5.8 GHz for applications based Autotracking antenna signal level. Systematics design includes mechanisms of designing antenna design simulation results using CST Microwave Studio Software, fabrication, measurement parameters such as return loss, VSWR, gain, Bandwitdh and Radiation Pattern, peformansi Testing and application of antenna. 1 helix antenna measurement results obtained value -17.84 dB Return Loss, VSWR 1.294, 14.53 dB Gain, Bandwitdh 300 MHz. 2 helix antenna obtained value -17.31 dB Return Loss, VSWR 1.315, 15.49 dB Gain, Bandwitdh 300 MHz, Helix Antenna 3 obtained value -18.88 dB return loss, VSWR 1.256, 15.97 dB Gain, Bandwitdh 240 MHz and shaped radiation pattern unidirectional. The test results Autotracking Antenna system based signal levels have a pretty good angle accuracy with a percentage error of the corner angle toward the target of 0.83%.